Peran Media Pembelajaran Kreatif Dalam Peningkatan Keterampilan Sains Anak Usia Dini di Kelurahan Kebonsari, Kecamatan Citangkil, Kota Cilegon - Siti Hanan; Sherin Ramadhania; Asih Setyo Rini; Lucky Setiawan; Sri Sukmawati; Yolla Sukma Handayani; Asep Rahmatullah (Universitas Maritim AMNI Semarang, 2024)
The lava lamp exercise with the children of kebonsari urban village, citangkil sub-district is a fun and educational activity that involves making simple lava lamps using materials easily found at home. This study aims to explore the children's experience of the lava lamp experiment, and its impact on their understanding of basic chemistry concepts, and chemical interactions. Through a teaching approach based on simple science experiments and participatory observation, children were given the opportunity to experiment with a mixture of oil, water, and coloring agents to create interesting visual effects in their own lava lamps. The results showed that this practice not only increased children's interest in science, but also strengthened collaborative skills, and understanding of basic experimental concepts. This experiment highlights the importance of experiential and interactive learning approaches in developing childrens I nterest in science.